Bibliometric analysis of occupational exposure in operating room from 1973 to 2022 - Li, Chuang; Geng, Meng; Li, Shujun; Li, Xianglan; Li, Huiqin; Yuan, Hufang; Liu, Fengxia (Journal of occupational medicine and toxicology (London, England), 2024)
Objective The purpose of this study is to identify and visualize from different perspectives the topic on occupational exposure in operating room (OEOR). Methods In the Web of Science Core Collection (WoSCC), all the half-century data were retrieved from January 1st, 1973 to December 31st, 2022. CiteSpace, VOSviewer and Excel 2019 were employed to analyze and visualize data, based on publications, countries, institutions, journals, authors, keywords. Result A total of 336 journal papers were found. The increase of publications virtually started in 1991, peaked in 2020 and has been slowing down ever since. USA played most significant part among all the 49 countries/regions, while Universidade Estadual Paulista out of 499 institutions published the most papers. International Archives of Occupational and Environmental Health bears the most documents and citations in all the 219 retrieved journals. There are 1847 authors found, among whom Hoerauf K is the most influential one. "Occupational exposure”, “nitrous oxide” and “operating room personnel” are the top 3 co-occurrences keywords. Conclusion The trend in the field lies in “anaesthetic gas”, “blood borne pathogen”, “radiation” and “aerosol”, while “surgical smoke” and “occupational safety” are the recently researching hot spots in this study. Accurate recognize and effective protection are always essential subjects for researchers.